1985
DOI: 10.1029/ja090ia01p00137
|View full text |Cite
|
Sign up to set email alerts
|

Ion and electron heating at collisionless shocks near the critical Mach number

Abstract: The evolution of the ion and electron distribution functions across a set of 10 low‐Mach number, nominally subcritical, quasi‐perpendicular shocks is examined in high time resolution (full distribution every 3 s) using data from the ISEE 1 and 2 spacecraft. Both ions and electrons sometimes show slight preheating upstream of the shock, but otherwise the ion and electron temperatures rise together in the magnetic ramp and show no further increase downstream. Contrary to the usual assumption based on early labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
98
2

Year Published

1986
1986
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 151 publications
(113 citation statements)
references
References 40 publications
13
98
2
Order By: Relevance
“…An important role in the dissipation process is played by ions reflected at the bow shock (Sckopke et al, 1983;Thomsen et al, 1985). At quasi-parallel shocks, they can escape from the shock into the foreshock region and drive ion beam instabilities.…”
Section: Introductionmentioning
confidence: 99%
“…An important role in the dissipation process is played by ions reflected at the bow shock (Sckopke et al, 1983;Thomsen et al, 1985). At quasi-parallel shocks, they can escape from the shock into the foreshock region and drive ion beam instabilities.…”
Section: Introductionmentioning
confidence: 99%
“…The standard view of wave-particle interactions is that enhanced fluctuations from an instability scatter particles to reduce the anisotropies which lead to wave growth. Thomsen et al [1985]), heating by instabilities driven by interplanetary pickup ions , and heating by proton/proton instabilities [Schwartz et al, 1981]. Gary et al [1986] showed that the magnetosonic instability at n• • nc does not induce a significant core anisotropy, but until now there have been no simulation studies to determine whether the Alfv•n instability is a plausible source of this anisotropy.…”
mentioning
confidence: 99%
“…Earlier studies on the ion dynamics at the Earth's bow shock point out that the following features are commonly observed for both critical and supercritical shocks (Thomsen et al, 1985;Sckopke et al, 1990 and references in these papers): (1) ions reflected from the shock rump and accelerated by the solar wind electric field in the foot region; (2) sharp broadening of ion distribution (heating) at the shock rump; (3) gyrating ions in the downstream region; (4) their relaxation leading to the high energy non-Maxwellian tail in the depth of downstream region; (5) the observed ratio of proton heating exceeds the adiabatic level. These phenomena typically observed in the near-Earth space resemble those presented in this paper.…”
Section: Discussionmentioning
confidence: 99%